Penerapan Penerapan Problem-Based Learning untuk Hasil Belajar Siswa Pada Instalasi Motor Listrik - Pratama, Riski Aditia; Taali, Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research was based on a problem related to the teaching and learning process which is still teacher-centred and lacks variation in the teaching and learning process. The Problem-Based Learning model is present as a solution in increasing the role and participation of students and giving birth to more varied learning. This research aims to determine the presentation value of improving learning outcomes and KKM completion before and after implementing the Problem-Based Learning Model. This research uses a quantitative approach with a Pre-Experimental type using a one-group pretest posttest design. The subjects in this research were students of class XI TITL C SMKN 1 Padang. The instruments used were pretest and posttest questions. The object of this research is the Problem-Based Learning Model to improve the learning outcomes of class XI TITL C students at SMKN 1 Padang. This research will look at how presentation scores increase learning outcomes and student learning completion before and after the implementation of the Problem-Based Learning model as measured by pretest and posttest sheets. The results of the pretest and posttest scores will be used in calculating the N-Gain Score test. It can be concluded that the increase in learning outcomes that occurred after implementing the Problem-Based Learning Model was high.